Study of genetic diversity of Salmonella typhi using pulsed-field gel electrophoresis (Faculty of Medicine Universitas Indonesia, 2001)
DNA genomes of Salmonella typhi (S. typhi), which were isolated from sporadic typhoid fever cases who were hospitalized in Persahabatan Hospital, Jakarta, during the 1st semester of 1998, were examined for their genetic diversities. Pulsed-field gel electrophoresis (PFGE) of genomic DNA digested with Xbal was performed for 25 isolates. Electrophoresis patterns of most isolates varied and 18 PFGE types were identified. Cluster analysis showed that all isolates originated from two main groups; and at ≥84% level of similarity, 7 clusters were found. Thus, the results showed that genetic diversity of S. typhi was considerably high, and that S. typhi isolated from sporadic typhoid fever cases were derived from multiple clones. (Med J Indones 2001; 10: 158-63)